PENGARUH MODEL PEMBELAJARAN TEAM GAME TOURNAMENT (TGT) TERHADAP AKTIVITAS DAN HASIL BELAJAR SISWA PADA MATERI NILAI MUTLAK - Hajar, Tasriqah Siti; Yusmin, Edy; Yani, Ahmad (Universitas Tanjungpura, 2024)
This study aims to find out the effect of the Teams Game Tournament (TGT) learning model on student activities and learning outcomes on Absolute Value study material in class X of MAS Rahmatan Lil Alamin. The research method used in this study is a quantitative method with a type of research that uses a quasi-experimental form. The research design used is the Non-Equivalent Control Group Pretest-Posttest. The techniques used are observation techniques and measurement techniques in the form of tests to observe student learning outcomes with data collection tools including student activity observation sheets and student learning outcome tests. The results of the calculation of student learning activities in the classroom categorize those that are given the treatment as